2008
DOI: 10.1080/17453670710014932
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported functional outcome after primary total hip replacement treated with two different periopera-tive regimes: A follow-up study involving 61 patients

Abstract: Background and purpose Fast-track surgery has been reported to improve rehabilitation outcome after major surgery, with length of hospitalization and muscle strength as outcome measures. We assessed the effect of optimization of perioperative care during admission on self-reported functional outcome, and compared patient status 6 months after THR with an age-matched healthy cohort.Patients and methods 79 THR patients were randomized to optimized perioperative care (OPC) or conventional perioperative care (CPC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Conventional perioperative care regimes have not been shown to be superior to fast-track setup in improvement of patient activity or QoL after 6 mo or longer. 12,13 Some results might suggest a need for more preoperative or early postoperative physical intervention during the first 3 mo. 13 Besides oral analgesics, patients were offered local infiltration analgesia during the first 24 h after surgery.…”
Section: Qol Hip Function and Painmentioning
confidence: 95%
See 2 more Smart Citations
“…Conventional perioperative care regimes have not been shown to be superior to fast-track setup in improvement of patient activity or QoL after 6 mo or longer. 12,13 Some results might suggest a need for more preoperative or early postoperative physical intervention during the first 3 mo. 13 Besides oral analgesics, patients were offered local infiltration analgesia during the first 24 h after surgery.…”
Section: Qol Hip Function and Painmentioning
confidence: 95%
“…Previous studies have demonstrated the benefit of THA on both QoL and function of the hip with follow-ups of more than 6 mo. 12,13,21 Very few authors have discussed how patients perform and cope with the principles of fast-track surgery. Conventional perioperative care regimes have not been shown to be superior to fast-track setup in improvement of patient activity or QoL after 6 mo or longer.…”
Section: Qol Hip Function and Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 12 RCTs (21 articles due to multiple publications) were included in published systematic reviews discussed in the systematic reviews section above and will not be discussed here further. 36,[38][39][40][41][42][44][45][46][47][48][49][50][51][52][53][54][55][56][57]61 Another 12 RCTs (13 articles) that were not included in the systematic reviews are discussed here separately. [58][59][60][62][63][64][65][66][67][68][69][70][71] Two foreign-language articles were identified: one Russian 72 and one Chinese.…”
Section: Randomised Controlled Trialsmentioning
confidence: 99%
“…Pre-emptive pain management programs using NSAIDS or COX-2 medications and dexamethasone can shorten hospital stay and decrease the likelihood of discharge to a skilled nursing facility but not all studies confirm these findings [2,3,5,6,9,17]. Several reports have reached conflicting conclusions regarding the efficacy of earlier physical therapy on discharge [7,8,10,[12][13][14]16]. Similarly, pre-operative patient education programs have demonstrated a varying contribution to decreased LOS [12-15, 18, 19].…”
Section: Introductionmentioning
confidence: 99%